Poverty in Mexico : An Assessment of Conditions, Trends, and Government Strategy - World Bank (World Bank, Mexico, D.F., 2013)
This report presents the results of an assessment of poverty conditions in Mexico, and of the Government strategies to reduce poverty. It constitutes the first phase of a longer-term work program on poverty reduction in Mexico that the Bank is undertaking in collaboration with the Government during the period 2003-2006. The current situation in the country is mixed, with respect to poverty. In terms of well-being, Mexico has experienced major progress in some dimensions - notably related to basic service access - but much weaker progress on others - notably on the income of the poor. Despite the gains between 1996 and 2002, and in particular, for the extreme poor, poverty remains widespread, and is only slightly below the levels prevailing before the 1994-1995 crisis. The report relates to government strategy, and its strengths. The CONTIGO framework is excellent as a conceptual framework, especially in its attempt to integrate the multiple dimensions of well-being, and public action into a life-cycle approach. There are notable successes in specific programs -with "Oportunidades" (i.e., "Opportunities ") unusual in its combination of highly effective targeting, and broad reach amongst the extreme poor. The emphasis on evaluation is commendable, while the recent introduction of the Ley de Desarrollo Social (Social Development Law) is a potentially valuable attempt to institutionalize the social development strategy, and in particular, provide more continuity across government administrations. But challenges still remain. The quality of services is a major issue in many sectors, for although social policies for the extreme poor are well developed, policies for their income growth are not. There is a broader pending agenda for the moderate poor, especially with respect to improving the productivity of the self-employed and informal enterprises. Most of the extreme and moderate poor fall outside the formal social protection system, and face significant risks, i.e., health, unemployment or lack of income in old age. And there are a wide range of institutional issues to be tackled - from strengthening accountability, especially under decentralized structures, to social incorporation of excluded groups - as well as linking of rigorous evaluation to results-based management.